Retinoblastoma mutation predicts poor outcomes in advanced non small cell lung cancer. (17th February 2019) - Bhateja, Priyanka; Chiu, Michelle; Wildey, Gary; Lipka, Mary Beth; Fu, Pingfu; Yang, Michael Chiu Lee; Ardeshir‐Larijani, Fatemeh; Sharma, Neelesh; Dowlati, Afshin
Abstract: The retinoblastoma gene ( RB1 ) encodes the retinoblastoma (RB) pocket protein that plays an important role in cell cycle progression. Here we determine the frequency and prognostic significance of RB1 mutation in non small cell lung cancer (NSCLC), restricting inclusion to Stage III and IV patients with linked genomic and clinical data. The primary outcome was median overall survival (OS). We identified RB1 mutation in 8.2% of NSCLC patients. The median OS for wild‐type (wt) RB1 was 28.3 months vs 8.3 months for mutant RB1 (Hazard Ratio = 2.59, P  =   0.002). Of special interest, RB1 mutation also correlated with lack of response to immunotherapy. Our study focused on RB1 mutation in locally advanced and advanced non small cell lung cancer to better facilitate comparisons with small cell lung cancer (SCLC). In our SCLC cohort, RB1 mutation was identified in 75% of patients and wt RB1 was associated with significantly shorter OS ( P  =   0.002). The different outcomes of RB1 mutation observed among lung cancer subtypes suggest a more complicated mechanism than simple regulation of cell cycle or response to chemotherapy. Abstract : Our study shows that retinoblastoma ( RB1 ) mutation is associated with decreased overall survival in patients with locally advanced and advanced non small cell lung cancer. We also show that RB1 mutation correlates with lack of response to immunotherapy.